EXAMINING THE ROLE OF KEY TOURISM DRIVERS CONTRIBUTING TO DESTINATION BRANDING AND MARKETING IN MANIPUR, INDIA (CAHIERS MAGELLANES-NS, 2024)
This study aims to examine the pivotal tourism drivers crucial for branding and marketing tourism in Manipur from the perspective of the local community. The study used both primary and secondary data and surveyed residents with a structured questionnaire. The data was analysed using the fourth version of Smart PLS. the key findings underscored the considerable significance of all attractions and accessibility attributes, highlighting their direct impact on travel motivation. The study asserted that the appropriate upkeep of tourist sites, the introduction of entertainment programs and events, and the enhancement of service quality and infrastructure facilities would significantly influence the branding and marketing of Manipur tourism. It is anticipated that this study will aid service providers in effectively branding and marketing Manipur as a tourist destination. Furthermore, the study recommends that policymakers to focus on creating long-term destination planning and development, with a special emphasis on critical tourism drivers. It further emphasises the importance of concentrating on key aspects of tourism as well as the systematic process of branding and marketing. Finally, the research concludes that eco-tourism represents the optimal approach for the branding of Manipur tourism.